Dupuytren Disease Management Trends: A Survey of Hand Surgeons. (January 2020) - Carr, Logan; Michelotti, Brett; Brgoch, Morgan; Hauck, Randy; Ingraham, John
Background: Indication for intervention in Dupuytren disease is influenced by many factors, including location and extent of disease, surgeon preference, and comfort level with different treatment techniques. The aim of this study was to determine current Dupuytren disease management trends.Methods: A questionnaire was sent through the American Society for Surgery of the Hand to all members. In addition to demographic data, questions focused on indications for different procedural interventions based on location of disease, age, and activity level of the patient.Results: Approximately 24% of respondents completed the survey. Respondents were mostly orthopedic surgeons in private practice who do not work with residents or fellows. Respondents preferred collagenase over needle aponeurotomy and limited fasciectomy for primary Dupuytren disease involving only the metacarpophalangeal (MCP) joint. Limited fasciectomy was the preferred treatment for primary Dupuytren disease involving the MCP and proximal interphalangeal joints. For a patient amenable to any treatment option, the majority would use collagenase, although 87.1% felt that fasciectomy offered the longest disease-free interval. Furthermore, given the option of a young, working patient, 42.7% would use collagenase, while plastic and general surgeons were more likely to treat this patient with limited fasciectomy. More plastic surgeons (vs orthopedic) believe that limited fasciectomy yields the longest disease-free interval. For a patient amenable to any surgical option, orthopedic surgeons prefer collagenase, whereas plastic hand surgeons prefer a limited fasciectomy.Conclusion: There are several procedural options for the treatment of Dupuytren disease. This study details current practice patterns among hand surgeons and reveals the increasingly prevalent use of collagenase.